Vibrational fatigue failure prediction of a brake caliper used for railway vehicles based on frequency domain method. Issue 1 (June 2021) - Zeng, Liangbin; Zhao, Jinliang; Meng, Yongshuai
Abstract: A brake caliper used for railway vehicles was introduced in this paper. In order to predict the fatigue failure under random vibration condition, firstly a dynamic model was established and proved by comparing the results of modal simulation and modal test. The weak points of the structure were identified by taking random response analysis, and the corresponding PSD (power spectral density) spectrums of stress were obtained. Furthermore three different PDF (probability density function) models of stress amplitude distribution were employed to describe the distributions of stress at weak points, then the fatigue damages were calculated based on Miner's linear cumulative damage theory and the fatigue failures were predicted. Finally, an accelerated failure test was designed and carried out to verify the validity of the predictions proposed by three models. The result shows that, the Dirlik's model and Steinberg's model can provide more exact results and be suitable for vibration fatigue failure prediction of brake caliper.